How do you solve using gaussian elimination or gauss-jordan elimination, 2x + y - z = -22x+yz=2, x + 3y + 2z = 4x+3y+2z=4, 3x + 3y - 3z = -103x+3y3z=10?

1 Answer

(x,y,z)=(4/3,-4/3,10/3)(x,y,z)=(43,43,103)

Explanation:

So let's make the matrix of the system, which is :

[(2,1,-1,-2),(1,3,2,4),(3,3,-3,-10)]

Now let's do our calculations :

[(2,1,-1,-2),(1,3,2,4),(3,3,-3,-10)]rarr[(1,-2,-3,-6),(1,3,2,4),(0,-6,-9,-22)]rarr

[(1,-2,-3,-6),(0,5,5,10),(0,-6,-9,-22)]rarr[(1,-2,-3,-6),(0,1,1,2),(0,-6,-9,-22)]rarr

[(1,-2,-3,-6),(0,1,1,2),(0,0,-3,-10)]rarr[(1,0,-1,-2),(0,1,1,2),(0,0,1,10/3)]rarr

[(1,0,0,4/3),(0,1,0,-4/3),(0,0,1,10/3)]

So we get : (x,y,z)=(4/3,-4/3,10/3)

(Just check my aritmetic, I tend to make mistakes)